Adapting MOVED as a web-based moral elevation intervention for veterans with PTSD: Using feedback from a pilot trial and subject matter experts - Adam P. McGuire; Alexander Riera; Xrystyan Lascano (Contemporary Clinical Trials Communications)
Background: Alternative, easily accessible treatment options are needed to aid efforts to address the negative effects of PTSD among veterans. One approach that has shown promise in a pilot trial is a moral elevation-based intervention titled, MOVED. Qualitative feedback from veterans in the pilot trial identified several strengths, but also highlighted opportunities to improve the intervention. In this adaptation phase, we incorporated feedback from pilot participants with input from subject matter experts (SMEs) to inform adaptation decisions using the Model for Adaptation Design and Impact (MADI) framework. In this paper, we outline the process and final adaptations decisions in preparation for a future efficacy trial to assess the impact of MOVED on targeted outcomes for veterans with PTSD. Method: We identified 10 SMEs that included veterans, clinicians, and researchers who participated in workgroup meetings to review 17 identified issues from the pilot and potential adaptations to address those concerns. We used the MADI framework to guide workgroup meeting discussions to determine what changes should be incorporated, including identifying potential negative outcomes for any adaptations and if they can be mitigated with other actions. Results: SMEs agreed with proposed adaptations for 15 of 17 issues and proposed mitigating measures for four of those adaptations to avoid anticipated negative outcomes. Two proposed solutions were refuted and not selected for adaptation. Conclusions: Using the MADI framework with input from SMEs allowed us to make informed decisions about adaptations for MOVED, thus contributing to further treatment development in preparation for a future efficacy trial.